Implementasi Metoda Coaching Pada Feedback Assessment Untuk Menurunkan GAP Kompetisi - Primiarna Primiarna (Sekolah Tinggi Teknik - PLN, 2020)
To prepare the ability of human resources, HR competencies are needed that are suitable both in terms of hard competency or soft competency. In order to develop themselves, they must know what are their strengths and weaknesses. The means to find out the strengths and weaknesses of PLN itself is carried out by individual feedback mechanisms. After participating in the assessment activities, employees will be given the results of the assessment. Notification of the results of the assessment is given verbally which usually includes feedback. In individual feedback, it will be told about what are the strengths, what are the weaknesses and how to reduce the competency gap they have. During this time the way to reduce the competency gap is given directly by the feedbacker. There is one method so that feedbackee (who is given feedback in this case the user who has followed the assessment) is easy to implement how to close the gap, that is, if the way to close the gap is out of the ideas of the asesee themselves, of course with the guidance of the feedbacker who knows the science of how to eliminate the gap competence. The method that matches the above method is the coaching method. The results obtained using the coaching method in the feedback assessment activities become a more effective solution to reduce the competency gap.